Preprosthetic surgery: An adjunct to complete denture therapy - Medha Vivek Bhuskute; Ravi G K Shet (Wolters Kluwer Medknow Publications, 2019)
Pre-prosthetic surgery is an integral part of Complete denture Prosthodontics. The ultimate goal of pre-prosthetic surgery is to prepare a mouth to receive a dental prosthesis by redesigning and smoothening bony edges which would otherwise cause hindrance in restoration of optimum health and function. This case report discusses how reduction of severe bony prominences and smoothening of irregular ridges resulted in achieving a better denture foundation which if left untreated otherwise would have resulted in sore spots and immense discomfort to the patient.